Adhesive and manufacturing method thereof, separator, electrode assembly, battery cell, battery and power consuming device
Patent Information
- Application Number
- JP2024500370
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-01-04
- Filing Date
- 2023-06-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-06-13
Smart Images

Figure 2025505077000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the field of battery technology, and in particular to adhesives and methods for making same, as well as separators, electrode assemblies, battery cells, batteries and power consuming devices.
[0002] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to a Chinese patent application filed on January 4, 2023, bearing application number 202310010649.0, the entire contents of which are incorporated herein by reference. [Background technology]
[0003] With the rapid increase in portable electronic devices, electric vehicles, etc., the demand for power batteries is constantly increasing, and the electrochemical performance of batteries is also attracting more and more attention.
[0004] Currently, the battery core of the battery has an opening problem, that is, gaps easily form between the plates and the separator, which leads to poor battery cycling performance. Summary of the Invention
[0005] The main object of the present application is to provide an adhesive that is intended to improve the adhesive strength between the separator and the electrode plate, thereby improving the cycle performance of the battery.
[0006] To achieve the above object, the present application provides an adhesive, the adhesive comprising a capsule shell and a core material disposed within the capsule shell, the capsule shell comprising an organic polymer, and the core material comprising a plasticizer.
[0007] According to the adhesive of the present application, the adhesive includes a capsule shell and a core material provided in the capsule shell, the capsule shell includes an organic polymer, and the core material includes a plasticizer. By coating the organic polymer capsule shell with the plasticizer as a core material, the adhesive performance of the organic polymer is improved, and the adhesive improves the adhesive strength between the separator and the electrode plate.
[0008] Optionally, the mass ratio of the core material to the capsule shell is 1:(10-100), optionally 1:(20-90).
[0009] The capsule-shaped adhesive is mainly performed by the capsule shell, and prevents the capsule shell from being broken. The mass of the capsule shell is greater than that of the core material, ensuring the adhesiveness and stability of the capsule structure. The mass ratio of the core material to the capsule shell is 1:(10-100), and in the above 1:(10-100), the value includes the minimum and maximum values of this range, and each value between the minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, etc.
[0010] Optionally, the mass ratio of the core material to the capsule shell is 1:(20-90).
[0011] In the above 1:(20-90), the value includes the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, etc.
[0012] Optionally, the adhesive has a volume average particle size Dv50 of 0.5 μm-100 μm, optionally 7 μm-8 μm.
[0013] Theoretically, the volume average particle diameter Dv50 of the adhesive in the present application may be less than 0.5 μm or more than 100 μm. However, considering that the adhesive in the present application is used in a separator, the volume average particle diameter Dv50 of the adhesive cannot be too large or too small. If the adhesive is too small, it is easy to block the pores of the separator, reducing the permeability of lithium ions through the separator. If the adhesive is too large, a thick coating will be formed when the adhesive is applied to the separator, which will cause the deterioration of the battery produced later. In order to affect the energy density, the volume average particle diameter Dv50 of the adhesive is 0.5 μm-100 μm, and in the above 0.5 μm-100 μm, the value includes the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc.
[0014] Optionally, the adhesive has a volume average particle size Dv50 of 7 μm-8 μm.
[0015] When the volume average particle diameter Dv50 of the adhesive is 7 μm-8 μm, the performance of the resulting separator is excellent, and in the above 7 μm-8 μm, the values include the minimum and maximum values of this range, and each value between such minimum and maximum values, and specific examples include, but are not limited to, the point values in the examples and 7 μm, 7.5 μm, 8 μm, etc.
[0016] Optionally, the capsule shell comprises at least one of a polyacrylate-based polymer and a urea-formaldehyde resin.
[0017] The capsule shell of the present application needs to have adhesive properties, and since polyacrylate-based polymer and urea-formaldehyde resin have relatively good adhesive properties, they can provide a better adhesive effect as a capsule shell. Of course, the capsule shell material of the present application is not limited, and any other material having relatively good adhesive properties and stability can be applied to the present application.
[0018] Optionally, the constituent monomers of the polyacrylate-based polymer include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight adjusting monomer.
[0019] The constituent monomers of the polyacrylate polymer in the present application include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight adjusting monomer. By crosslinking the three types of monomers to obtain a polymer, the molecular weight and glass transition temperature of the polymer can be controlled, thereby improving the adhesive performance of the adhesive.
[0020] Alternatively, the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), and optionally 1:(0.05-0.7):(0.05-0.12).
[0021] When the molar ratio of the first polymerizable flexible monomer, the second polymerizable polar monomer, and the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), the adhesive has excellent adhesion effect. In the above 1:(0.01-0.8):(0.01-0.15), the values include the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples are the point values in the examples and 1:0. This includes, but is not limited to, 01:0.01, 1:0.1:0.01, 1:0.4:0.01, 1:0.8:0.01, 1:0.01:0.05, 1:0.01:0.1, 1:0.01:0.15, 1:0.1:0.01, 1:0.1:0.05, 1:0.1:0.15, 1:0.4:0.01, 1:0.4:0.05, 1:0.4:0.15, 1:0.8:0.01, 1:0.8:0.05, 1:0.8:0.15, etc.
[0022] Optionally, the molar ratio of the first polymerizable flexible monomer, the second polymerizable polar monomer, and the third polymerizable molecular weight adjusting monomer is 1:(0.05-0.7):(0.05-0.12).
[0023] When the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.05-0.7):(0.05-0.12), the adhesive has excellent adhesion effect. In the above 1:(0.05-0.7):(0.05-0.12), the values include the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:0.05:0.05, 1:0.1:0.05, 1:0.4:0.05, 1:0.7:0.05, 1:0.1:0.05, 1:0.1:0.1, 1:0.1:0.12, etc.
[0024] Optionally, the structure of the first polymerizable flexible monomer contains an ester bond, the structure of the second polymerizable polar monomer contains a cyano group, and the structure of the third polymerizable molecular weight adjusting monomer contains an amide bond.
[0025] The ester bond can improve the flexibility of the molecular chain, the cyano group can improve the polarity of the monomer, and the amide bond has polarity and is easy to form hydrogen bonds, which can improve the adhesiveness. The first polymerizable flexible monomer contains an ester bond in its structure, the second polymerizable polar monomer contains a cyano group in its structure, and the third polymerizable molecular weight adjusting monomer contains an amide bond, so that the polymer obtained by polymerizing the above three types of monomers can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.
[0026] Optionally, the first polymerizable flexible monomer is an acrylate-based monomer, the second polymerizable polar monomer is an acrylonitrile-based monomer, and the third polymerizable molecular weight adjusting monomer is an acrylamide-based monomer.
[0027] The acrylate monomer can improve the swelling resistance of the polymer, and can adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, thereby improving the toughness of the adhesive when applied, thereby contributing to the exertion of a good adhesive action.
[0028] The acrylonitrile monomer has a cyano group with strong polarity, which contributes to improving the ion conductivity and the adhesiveness.
[0029] The acrylamide monomer not only serves to adjust the molecular weight, but also has relatively good adhesive properties.
[0030] The polymer obtained by the above three kinds of monomers can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.
[0031] Alternatively, the acrylate monomer may include at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate; and / or the acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile; And / or, the acrylamide-based monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide.
[0032] The acrylate monomer contributes to improving the adhesive properties of the adhesive. The acrylate monomer may include at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. In other words, the constituent monomers of the polyacrylate polymer may include one of the above acrylate monomers, or may include multiple acrylate monomers, and are not specifically limited.
[0033] The acrylonitrile-based monomer contributes to improving the adhesive properties of the adhesive, and the acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile. In other words, the constituent monomers of the polyacrylate-based polymer may include one of the above acrylonitrile-based monomers or may include multiple of the above acrylonitrile-based monomers, and are not specifically limited.
[0034] The acrylamide monomer contributes to improving the adhesive properties of the adhesive, and the acrylamide monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide. In other words, the constituent monomers of the polyacrylate polymer may include one of the above acrylamide monomers or may include multiple acrylamide monomers, and are not specifically limited.
[0035] Optionally, the plasticizer comprises at least one of dibutyl phthalate, dioctyl adipate, dibutyl sebacate, dioctyl sebacate, di-n-butyl adipate.
[0036] The core material is a plasticizer-based material, and the plasticizer may be any commonly used plasticizer, and is not limited to a specific type. For example, the core material may include at least one of dibutyl phthalate, dioctyl adipate, dibutyl sebacate, dioctyl sebacate, and di-n-butyl adipate.
[0037] The present application provides a method for producing an adhesive, mixing and stirring water, an emulsifier and constituent monomers of an organic polymer to obtain a prepolymer, which is kept as a reserve; Mixing and stirring water, an emulsifier, and a plasticizer to obtain an emulsion, which is then reserved; The prepolymer and an initiator are added to the emulsion and reacted by heating to obtain an adhesive, the adhesive including a capsule shell and a core material disposed within the capsule shell, the capsule shell including an organic polymer, and the core material including a plasticizer.
[0038] In the present application, a capsule-shaped adhesive is obtained by emulsion polymerization, in which an emulsion of a capsule shell prepolymer and a core material is prepared respectively, and then the prepolymer and an initiator are dropped into the emulsion and reacted by heating, so that the capsule shell prepolymer forms a polymer on the surface of the core material to obtain a capsule-shaped adhesive.
[0039] Optionally, the organic polymer includes at least one of a polyacrylate-based polymer and a urea-formaldehyde resin.
[0040] Without being limited to the type of organic polymer in this application, the organic polymer must have adhesive properties, and may be, for example, a polyacrylate-based polymer or a urea-formaldehyde resin.
[0041] Optionally, the ratio of the mass of the plasticizer to the mass of the constituent monomer of the organic polymer is 1:(10-100), and optionally 1:(20-90).
[0042] The capsule-shaped adhesive is mainly performed by the capsule shell, and prevents the capsule shell from being broken. The mass of the capsule shell is greater than that of the core material, ensuring the adhesiveness and stability of the capsule structure. The mass ratio of the core material to the capsule shell is 1:(10-100), and in the above 1:(10-100), the value includes the minimum and maximum values of this range, and each value between the minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, etc.
[0043] Optionally, the ratio of the mass of the plasticizer to the mass of the constituent monomer of the organic polymer is 1:(20 to 90).
[0044] In the above 1:(20-90), the value includes the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, etc.
[0045] An embodiment of the present application provides a separator, on which an adhesive as described above or an adhesive obtained by the manufacturing method of the adhesive as described above is provided.
[0046] The separator is coated with the above adhesive, which can improve the adhesive performance between the electrode plate and the adhesive and improve the opening problem in the conventional battery core pre-cold pressing process.
[0047] An embodiment of the present application provides an electrode assembly, the electrode assembly including the separator described above.
[0048] The electrode assembly includes a positive electrode plate, a negative electrode plate, and a separator, and the adhesive is coated on the separator, thereby bonding the electrode plate and the separator together and improving the problem of openings between the electrode plate and the separator.
[0049] An embodiment of the present application provides a battery cell, which includes an electrode assembly as described above.
[0050] By applying the above electrode assembly to a battery cell, the cycle performance of the large jig of the battery cell can be improved.
[0051] An embodiment of the present application provides a battery, the battery including the battery cell described above.
[0052] An embodiment of the present application provides a power consuming device, the power consuming device including the above battery cell or the above battery. [Brief description of the drawings]
[0053] In order to more clearly explain the technical solutions in the embodiments of the present application or the prior art, the following briefly introduces drawings that need to be used in the embodiments or prior art description. It is obvious that the drawings in the following description are only some embodiments of the present application, and those skilled in the art can also obtain other drawings based on the structures shown in these drawings without exerting creative efforts. [Figure 1] 1 is a flow chart of a method for making an adhesive according to an embodiment of the present application. [Diagram 2] 1 is a flow chart of a method for making an adhesive according to an embodiment of the present application. [Diagram 3] FIG. 2 is a structural schematic diagram of an adhesive according to an embodiment of the present application. [Figure 4] 1 is a scanning electron microscope view of an adhesive according to an embodiment of the present application. [Diagram 5] FIG. 2 is a schematic diagram of an electrode assembly according to an embodiment of the present application. [Figure 6] FIG. 6 is an exploded view of an electrode assembly according to the embodiment of the present application shown in FIG. 5. [Figure 7] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Figure 8] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Figure 9] FIG. 9 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 8. [Figure 10] BRIEF DESCRIPTION OF THE DRAWINGS Fig. 1 is a schematic diagram of a power consuming device according to an embodiment of the present application.The realization of the objects, functional features and advantages of the present application will be further explained with reference to the drawings in conjunction with the embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0054] The following clearly and completely describes the technical solutions in the embodiments of the present application in conjunction with the drawings in the embodiments of the present application, and obviously, the described embodiments are only some of the embodiments of the present application, not all of the embodiments. All other embodiments obtained based on the embodiments of the present application without the need for creative efforts by those skilled in the art are all within the scope of protection of the present application.
[0055] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing an adhesive and a manufacturing method thereof, as well as a separator, an electrode assembly, a battery cell, a battery, and a power consumption device each including the adhesive will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0056] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is just a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0057] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0058] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0059] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.
[0060] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the ingredients listed.
[0061] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).
[0062] A lithium ion battery is composed of four parts: a positive electrode material, a negative electrode material, an electrolyte, and a separator. The separator is a functional membrane material with a micro-pore structure, generally 8μm to 40μm thick, which separates the positive and negative electrodes in the battery system, blocks the passage of electrons in the circuit during charging and discharging, and allows the lithium ions in the electrolyte to pass freely. When the battery is charged and discharged or the temperature rises, the micro-pores are selectively closed to limit overcurrent and prevent short circuits, and the superiority or inferiority of the performance directly determines the overall performance of the battery. Conventional lithium ion battery separators are polyolefin separators, and most of them have a single-layer or three-layer structure, such as single-layer PE, single-layer PP, PP / PE / PP composite membrane, etc. However, conventional lithium ion battery separators are non-polar and have poor direct adhesion effect with the positive and negative electrode plates, so they are often attached by coating their surfaces with adhesive. A commonly used adhesive is polyvinylidene fluoride, which is a homopolymer with a crystallinity of about 50%. Due to its relatively high crystallinity, the adhesive strength between the separator and the positive and negative electrodes is insufficient, which often causes the battery core to open up and has poor electrolyte permeability, and cannot meet the performance requirements of coated separators for power lithium-ion batteries.
[0063] The battery core is formed by bonding the positive and negative electrode plates and the separator, and the battery core has a certain hardness, that is, the bonded positive and negative electrode plates and the separator are supported by adhering to each other to form a structure with a certain thickness, so the structure with a certain thickness has a certain hardness, and the negative electrode expands during charging and discharging. If the adhesive strength is weak, a gap is formed between the positive and negative electrode plates and the separator, and the positive and negative electrode plates and the separator cannot be supported by adhering to each other, and the battery core becomes loose and the hardness is reduced, and at this time, the power performance of the battery core is deteriorated, for example, the rate performance is reduced and the cycle performance is deteriorated. For example, in an electric vehicle, the battery core of the battery becomes loose, the charging speed of the battery is slowed and the cycle performance of the battery is deteriorated, which directly causes the battery life to be shortened, and the electric vehicle needs to replace the battery frequently, which increases the cost of the electric vehicle for consumers.
[0064] Based on this, the present application proposes an adhesive, which includes a capsule shell and a core material disposed within the capsule shell, the capsule shell including an organic polymer and the core material including a plasticizer.
[0065] The organic polymer is a polymer obtained by polymerizing an organic monomer, and in the present application, is an organic polymer having adhesive properties.
[0066] An adhesive is a material that has adhesive properties for bonding dissimilar substances together.
[0067] The capsule shell structure is a covering structure for encasing the contents, and as shown in FIG. 3, the capsule shell structure 6 covers a core material 7.
[0068] Regarding plasticizers, their functions are mainly to weaken the divalent bonds between polymer molecules, increase the mobility of resin molecular bonds, reduce the crystallinity of resin molecules, increase the plasticity of resin molecules, and reinforce flexibility. Plasticizers are substances that can improve the physical properties of polymerization. The addition of plasticizers can reduce the interaction between polymer molecular chains, and reduce the glass temperature, flow temperature and melting point of the crystallites contained in the polymer. Plasticizers can improve the plasticity of resins and make products flexible, and have good low temperature resistance.
[0069] The present application uses a capsule shell structure to cover the plasticizer core material, obtains an adhesive with a capsule structure, and improves the overall flexibility of the adhesive with the capsule structure, thereby improving the adhesive performance, and the adhesive improves the adhesive strength between the separator and the electrode plate. The adhesive of the present application has good adhesive performance, does not separate the electrode plate and the separator during the expansion of the electrode plate, avoids problems such as opening of the battery core, and maintains good hardness of the battery core, improving the dynamic performance and cycle performance of the battery core.
[0070] For example, when the battery core is pre-cold pressed, the flexibility of the adhesive is improved, so that the adhesive can fully penetrate into the gap between the positive and negative electrode plates and the separator; that is, when there is a gap between the electrode plates and the separator, the adhesive penetrates into the gap and effectively connects the electrode plates and the separator, and the adhesive is not easily separated from the gap; during the expansion of the electrode plates, the adhesive has toughness and can effectively connect the two even during expansion; the adhesive can fully exert its adhesive performance, which further contributes to improving the dynamic performance of the battery and the cycle performance of the large jig.
[0071] In this application, the plasticizer is placed inside the capsule shell of the organic polymer, which can improve the uniformity of the distribution of the plasticizer compared to adding the plasticizer directly into the organic polymer. For example, if a plasticizer is added to an organic polymer monomer and polymerized, the plasticizer may be unevenly dispersed in the organic polymer. If the adhesive obtained by mixing and polymerizing the plasticizer is used for a separator, if the dispersion of the plasticizer is uneven, the separator may have good flexibility in some parts and poor flexibility in other parts, which may cause the performance of the entire separator to be unstable. However, by producing an adhesive with a capsule structure, an adhesive with a relatively uniform capsule structure containing a plasticizer core material can be obtained, which can improve the performance of the entire adhesive. This adhesive is advantageous for application to a separator to improve the performance of the entire separator.
[0072] When applying the adhesive to the separator, the adhesive needs to be premixed with other raw materials, and the premixed raw materials are water-based, and the plasticizer is an oily substance, so the plasticizer is exposed, resulting in poor mixing and dispersion, poor mixing uniformity, poor uniformity of the material applied to the separator, and poor separator performance. Therefore, by accommodating the plasticizer as a core material in the capsule shell, it is not only advantageous for the premixing operation, but also improves the overall performance of the separator.
[0073] In some embodiments, the mass ratio of the core to the capsule shell is 1:(10-100), optionally 1:(20-90).
[0074] The capsule-shaped adhesive is mainly performed by the capsule shell, and prevents the capsule shell from being broken. The mass of the capsule shell is greater than that of the core material, ensuring the adhesiveness and stability of the capsule structure. The mass ratio of the core material to the capsule shell is 1:(10-100), and in the above 1:(10-100), the value includes the minimum and maximum values of this range, and each value between the minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, etc.
[0075] In the mass ratio test method, when the mass of the monomer for producing the core layer structure, which is added during the reaction process in the manufacturing process of the adhesive, is recorded as m, and the mass of the monomer for producing the shell layer structure is recorded as n, the mass ratio of the core layer structure to the shell layer structure is m:n.
[0076] In some embodiments, the mass ratio of the core material to the capsule shell is 1:(20-90).
[0077] In the above 1:(20-90), the value includes the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, etc.
[0078] In some embodiments, the adhesive has a volume average particle size Dv50 of 0.5 μm-50 μm.
[0079] The volume average particle size Dv50 of the adhesive can be tested using methods known in the art, for example, see GB / T 19077-2016, characterization tests can be performed using Malvern laser particle sizers, for example, using instruments such as Malvern's Mastersizer-3000.
[0080] In some embodiments, the adhesive has a volume average particle size Dv50 of 0.5 μm-100 μm, optionally 7 μm-8 μm.
[0081] Theoretically, the volume average particle diameter Dv50 of the adhesive in the present application may be less than 0.5 μm or more than 100 μm. However, considering that the adhesive in the present application is used in a separator, the volume average particle diameter Dv50 of the adhesive cannot be too large or too small. If the adhesive is too small, it is easy to block the pores of the separator, reducing the permeability of lithium ions through the separator. If the adhesive is too large, a thick coating will be formed when the adhesive is applied to the separator, which will cause the deterioration of the battery produced later. In order to affect the energy density, the volume average particle diameter Dv50 of the adhesive is 0.5 μm-100 μm, and in the above 0.5 μm-100 μm, the value includes the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc.
[0082] In some embodiments, the adhesive has a volume average particle size Dv50 of 7 μm-8 μm.
[0083] When the volume average particle diameter Dv50 of the adhesive is 7 μm-8 μm, the performance of the resulting separator is excellent, and in the above 7 μm-8 μm, the values include the minimum and maximum values of this range, and each value between such minimum and maximum values, and specific examples include, but are not limited to, the point values in the examples and 7 μm, 7.5 μm, 8 μm, etc.
[0084] In some embodiments, the capsule shell comprises at least one of a polyacrylate-based polymer and a urea-formaldehyde resin.
[0085] A polyacrylate-based polymer is a polymer having acrylate monomers.
[0086] Urea-formaldehyde resin is produced by polycondensation of urea and formaldehyde under the action of a catalyst (basic or acidic catalyst) to form an initial urea-formaldehyde resin.
[0087] The capsule shell of the present application needs to have adhesive properties, and since polyacrylate-based polymers have relatively good adhesive properties, they can provide a better adhesive effect as capsule shells. Of course, the capsule shell material of the present application is not limited, and any other material having relatively good adhesive properties and stability can be applied to the present application.
[0088] By producing polymer capsules by coating a plasticizer with at least one of a polyacrylate polymer and a urea-formaldehyde resin, the synergistic effect of the two can be fully exerted. By coating the separator with this, the pre-cold press adhesive strength between the separator and the positive and negative electrode plates can be improved, and problems such as opening of the battery core can be avoided. Furthermore, by coating the separator with this adhesive and applying it to a lithium ion battery, the hardness of the battery core and the cycle performance of the lithium ion battery can be improved.
[0089] In some embodiments, the constituent monomers of the polyacrylate-based polymer include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight modifying monomer.
[0090] Regarding the flexible monomer, the homopolymer glass transition temperature of the flexible monomer is lower than that of the rigid monomer, and the flexible monomer has a certain flexibility relative to the rigid group, allowing the chain segment to move freely. The flexible monomer can adjust the glass transition temperature of the chain segment polymer and improve the toughness of the adhesive during application, which contributes to exerting good adhesive action.
[0091] A polar monomer is a monomer that contains a polar group, and the polar monomer contributes to improving the adhesiveness of the polymer.
[0092] The molecular weight adjusting monomer is a monomer that is involved in a crosslinking reaction and is used to adjust the molecular weight of the polymer. The molecular weight of the adhesive within a certain range contributes to improving the adhesive properties.
[0093] The constituent monomers of the polyacrylate polymer in the present application include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight adjusting monomer. By crosslinking the three types of monomers to obtain a polymer, the molecular weight and glass transition temperature of the polymer can be controlled, thereby improving the adhesive performance of the adhesive.
[0094] The softening point of the modified polymer is lowered, and the adhesive can fully penetrate into the gap between the positive and negative electrode plates and the separator; that is, when there is a gap between the electrode plates and the separator, the adhesive penetrates into the gap and effectively connects the electrode plates and the separator, and the adhesive is less likely to come out of the gap; during the expansion of the electrode plates, the adhesive has toughness and can effectively connect the two even during expansion; the adhesive can fully exert its adhesive performance, which further contributes to improving the dynamic performance of the battery and the cycle performance of the large jig.
[0095] Here, the softening point is the temperature at which a substance softens. It is related not only to the structure of a polymer but also to the size of its molecular weight. In the present application, the softening point of the polymer is improved by adjusting the molecular weight of the polymer with a third polymerization molecular weight adjusting monomer.
[0096] Here, the cycle performance of the large jig is a cycle functional test performance of a battery core. In the test process, a jig is attached to the battery core, and a certain force is applied to the jig to press the battery core. When the battery core is fully charged, expansion occurs, and the battery core is deformed due to the double compression of the clamping force and expansion force of the jig. This test is used to test the shape retention performance and pressure resistance performance of the battery core. When the adhesive of the present solution is used, the adhesive performance is good, so the expansion of the battery core is weakened and the shape retention of the battery core is relatively good. The battery core using the adhesive of the present application has relatively good performance retention under the test conditions of the large jig, and the battery core obtained by using the adhesive of the present solution has excellent deformation retention. When the battery core is assembled to form a battery, the battery core is not easily deformed, so the space for installing the battery core in the battery can be saved, and the volume of the battery can be made smaller. Therefore, if the battery core is prone to deformation, it will press on the structure near the battery core; in order to avoid this phenomenon, a larger space is needed to accommodate the deformed battery core, that is, space in the battery needs to be reserved to accommodate the deformed part of the battery core, thereby occupying more space within the battery.
[0097] At the same time, it was explained that the good cycle performance of the large jig for the battery core also means that the cycle performance of the battery core is good. For example, if the battery core expands, the gap between the electrode plates and the separator becomes larger, the path through which lithium ions pass through the positive and negative electrodes becomes longer, and the cycle becomes worse.
[0098] In some embodiments, the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), optionally 1:(0.05-0.7):(0.05-0.12).
[0099] The molar ratio test method is to record the number of moles of each type of monomer used to produce the shell layer structure during the reaction process of the adhesive production, where the number of moles of each type of monomer is the mass of each type of monomer divided by the molecular weight of each type of monomer. The number of moles of the first polymerizable flexible monomer is defined as a, the number of moles of the second polymerizable polar monomer is defined as b, and the number of moles of the third polymerizable molecular weight adjusting monomer is defined as c, and the molar ratio of the first polymerizable flexible monomer, the second polymerizable polar monomer, and the third polymerizable molecular weight adjusting monomer is a:b:c.
[0100] When the molar ratio of the first polymerizable flexible monomer, the second polymerizable polar monomer, and the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), the adhesive has excellent adhesion effect. In the above 1:(0.01-0.8):(0.01-0.15), the values include the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples are the point values in the examples and 1:0. This includes, but is not limited to, 01:0.01, 1:0.1:0.01, 1:0.4:0.01, 1:0.8:0.01, 1:0.01:0.05, 1:0.01:0.1, 1:0.01:0.15, 1:0.1:0.01, 1:0.1:0.05, 1:0.1:0.15, 1:0.4:0.01, 1:0.4:0.05, 1:0.4:0.15, 1:0.8:0.01, 1:0.8:0.05, 1:0.8:0.15, etc.
[0101] In some embodiments, the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.05-0.7):(0.05-0.12).
[0102] When the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.05-0.7):(0.05-0.12), the adhesive has excellent adhesion effect. In the above 1:(0.05-0.7):(0.05-0.12), the values include the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:0.05:0.05, 1:0.1:0.05, 1:0.4:0.05, 1:0.7:0.05, 1:0.1:0.05, 1:0.1:0.1, 1:0.1:0.12, etc.
[0103] In some embodiments, the structure of the first polymerizable flexible monomer contains an ester bond (-COOR, where R is typically another non-H group such as an alkyl group), the structure of the second polymerizable polar monomer contains a cyano group (-C3N), and the structure of the third polymerizable molecular weight adjusting monomer contains an amide bond (-CO-NH-).
[0104] The ester bond can improve the flexibility of the molecular chain, the cyano group can improve the polarity of the monomer, and the amide bond has polarity and is easy to form hydrogen bonds, which can improve the adhesiveness. The first polymerizable flexible monomer contains an ester bond in its structure, the second polymerizable polar monomer contains a cyano group in its structure, and the third polymerizable molecular weight adjusting monomer contains an amide bond, so that the polymer obtained by polymerizing the above three types of monomers can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.
[0105] In some embodiments, the first polymerizable flexible monomer is an acrylate based monomer, the second polymerizable polar monomer is an acrylonitrile based monomer, and the third polymerizable molecular weight adjusting monomer is an acrylamide based monomer.
[0106] The acrylate monomer can improve the swelling resistance of the polymer, and can adjust the glass transition temperature of the polymer as a flexible monomer chain segment in the molecular chain segment, thereby improving the toughness of the adhesive when applied, thereby contributing to the exertion of a good adhesive action.
[0107] The acrylonitrile monomer has a cyano group with strong polarity, which contributes to improving the ion conductivity and the adhesiveness.
[0108] The acrylamide monomer not only serves to adjust the molecular weight, but also has relatively good adhesive properties.
[0109] The polymer obtained by the above three kinds of monomers can control the molecular weight and glass transition temperature of the polymer, thereby improving the adhesive performance of the adhesive.
[0110] In some embodiments, the acrylate based monomers include at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate; and / or the acrylonitrile based monomers include at least one of acrylonitrile and methacrylonitrile; and / or the acrylamide based monomers include at least one of acrylamide, N-methylol acrylamide, and N-butoxymethacrylamide.
[0111] The acrylate monomer contributes to improving the adhesive properties of the adhesive. The acrylate monomer may include at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate. In other words, the constituent monomers of the polyacrylate polymer may include one of the above acrylate monomers, or may include multiple acrylate monomers, and are not specifically limited.
[0112] The acrylonitrile-based monomer contributes to improving the adhesive properties of the adhesive, and the acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile. In other words, the constituent monomers of the polyacrylate-based polymer may include one of the above acrylonitrile-based monomers or may include multiple of the above acrylonitrile-based monomers, and are not specifically limited.
[0113] The acrylamide monomer contributes to improving the adhesive properties of the adhesive, and the acrylamide monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide. In other words, the constituent monomers of the polyacrylate polymer may include one of the above acrylamide monomers or may include multiple acrylamide monomers, and are not specifically limited.
[0114] In some embodiments, the plasticizer comprises at least one of dibutyl phthalate, dioctyl adipate, dibutyl sebacate, dioctyl sebacate, and di-n-butyl adipate.
[0115] The core material is a plasticizer-based material, and the plasticizer may be any commonly used plasticizer, and is not limited to a specific type. For example, the core material may include at least one of dibutyl phthalate, dioctyl adipate, dibutyl sebacate, dioctyl sebacate, and di-n-butyl adipate.
[0116] In some embodiments, as shown in FIG. 1, the present application further provides a method of making an adhesive, comprising: A step of mixing and stirring water, an emulsifier, and constituent monomers of an organic polymer to obtain a prepolymer and keep it as a reserve; A step of mixing and stirring water, an emulsifier, and a plasticizer to obtain an emulsion and reserve it; The method includes adding a prepolymer and an initiator to the emulsion and heating to react to obtain an adhesive, the adhesive including a capsule shell and a core material disposed within the capsule shell, the capsule shell including an organic polymer, and the core material including a plasticizer.
[0117] The present application uses emulsion polymerization to obtain a capsule-shaped adhesive, by first preparing an emulsion of a capsule shell prepolymer and a core material, respectively, and then adding the prepolymer and an initiator to the emulsion and heating to react, so that the capsule shell prepolymer forms a polymer on the surface of the core material to obtain a capsule-shaped adhesive.
[0118] Regarding emulsion polymerization, emulsion polymerization is a method in which a monomer is dispersed in water with an emulsifier by mechanical stirring to form an emulsion, and then an initiator is added to start the monomer polymerization.
[0119] About emulsifiers: Emulsifiers are substances that can convert incompatible oils and water into emulsions that are less likely to stratify. Emulsifiers are generally surface active agents that combine the properties of both hydrophilic polar groups and hydrophobic (lipophilic) non-polar groups.
[0120] Regarding initiators, initiators are substances capable of initiating the polymerization reaction of monomers. For example, radical initiators are compounds that are easily decomposed into radicals (i.e., primary radicals) by heat and may be used to initiate the radical polymerization and copolymerization reactions of ene and diene monomers.
[0121] For convenience of description, in the above adhesive manufacturing method, the process of the manufacturing method is divided into step 1, step 2, and step 3 according to the order of the described paragraphs. As can be understood by a person skilled in the art, in the above method of specific embodiments, the described order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process, and the specific execution order of each step should be determined according to its function and possible inherent logic.
[0122] In step 1, water, emulsifier, and organic polymer constituent monomers are mixed and stirred, and the water and emulsifier are stirred and dispersed to form an emulsion, that is, the emulsifier forms micelles in the water phase, and the monomers are solubilized in most of the micelles to obtain the prepolymer of the capsule shell; in step 2, water, emulsifier, and plasticizer are mixed and stirred to form an emulsion, and the emulsifier and water are similarly dispersed to form an emulsion, and the plasticizer enters the micelles to obtain an emulsion and reserve; in step 3, an initiator and prepolymer are added to the emulsion, and the mixture is stirred and heated to react, so that the constituent monomers of the polyorganic polymer form a polymer on the surface of the core material, and the organic polymer coats the core material, and an adhesive with a capsule structure is obtained.
[0123] Since a certain temperature is required for the initiator in step 3 to be converted to have the function of initiating monomer polymerization, step 3 is always carried out under heating conditions.
[0124] At the same time, in step 3, water may or may not be added; it can be understood that if enough water is added in steps 1 and 2, that is, the water added in steps 1 and 2 can make the solid content after the reaction in steps 1, 2 and 3 be within a preset range, then water may not be added in step 3; if not enough water is added in steps 1 and 2, a certain amount of water needs to be added in step 3 to adjust the solid content of the system, so as to prevent the viscosity after the reaction from becoming too large and the reaction rate from slowing down.
[0125] In some embodiments, the organic polymer comprises at least one of a polyacrylate-based polymer and a urea-formaldehyde resin.
[0126] Without being limited to the type of organic polymer in this application, the organic polymer should have adhesive properties, and may be, for example, at least one of a polyacrylate-based polymer and a urea-formaldehyde resin.
[0127] In some embodiments, as shown in FIG. 2, the ratio of the mass of the plasticizer to the mass of the constituent monomers of the organic polymer is 1:(10-100), optionally 1:(20-90).
[0128] The capsule-shaped adhesive is mainly performed by the capsule shell, and prevents the capsule shell from being broken. The mass of the capsule shell is greater than that of the core material, ensuring the adhesiveness and stability of the capsule structure. The mass ratio of the core material to the capsule shell is 1:(10-100), and in the above 1:(10-100), the value includes the minimum and maximum values of this range, and each value between the minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, etc.
[0129] In some embodiments, the ratio of the mass of the plasticizer to the mass of the constituent monomers of the organic polymer is 1:(20 to 90).
[0130] In the above 1:(20-90), the value includes the minimum and maximum values of this range, and each value between such minimum and maximum values. Specific examples include, but are not limited to, the point values in the examples and 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, etc.
[0131] In some embodiments, the step of mixing and stirring water, an emulsifier, and constituent monomers of the organic polymer to obtain and reserve a prepolymer includes the step of mixing and stirring water, an emulsifier, and constituent monomers of the organic polymer at a stirring rate of 1000 r / min to 5000 r / min for 60 min±20 min to obtain and reserve a prepolymer.
[0132] In order to obtain a sufficiently emulsified prepolymer, it is necessary to stir at a high speed for a certain period of time, that is, water, an emulsifier and a constituent monomer of an organic polymer are mixed and stirred, the stirring rate is 1000 r / min-5000 r / min, for example, 1000 r / min, 2000 r / min, 3000 r / min, 4000 r / min, 5000 r / min, etc., and is not specifically limited, and the stirring time is 60 min ± 20 min. Under these stirring conditions, a uniformly emulsified prepolymer is obtained and kept as a reserve.
[0133] In some embodiments, the step of mixing and stirring water, an emulsifier, and a plasticizer to obtain and reserve an emulsion includes the step of mixing and stirring water, an emulsifier, and a plasticizer at a stirring rate of 1000 r / min to 5000 r / min for 60 min±20 min to obtain and reserve an emulsion.
[0134] In order to sufficiently emulsify the plasticizer, it is necessary to stir at high speed for a certain period of time, that is, water, emulsifier, and plasticizer are mixed and stirred, and the stirring rate is 1000 r / min-5000 r / min, for example, 1000 r / min, 2000 r / min, 3000 r / min, 4000 r / min, 5000 r / min, etc., and is not specifically limited. Stir for 60 min±20 min to obtain an emulsion, which is kept as a reserve.
[0135] In some embodiments, in the step of mixing and stirring water, an emulsifier, and a plasticizer to obtain an emulsion and set it aside, the water and the emulsifier are mixed and stirred to obtain an emulsified solution, and a plasticizer is further added to the emulsified solution to continue stirring and emulsification, thereby obtaining an emulsion and setting it aside.
[0136] In order to better emulsify the plasticizer, first, water and emulsifier are mixed and stirred to obtain an emulsified solution, and then the plasticizer is added to the emulsified solution and emulsified by stirring to obtain an emulsion, which is kept as a reserve.
[0137] In some embodiments, the step of mixing and stirring water and an emulsifier to obtain an emulsified solution, further adding a plasticizer to the emulsified solution and continuing stirring and emulsification to obtain an emulsion and set aside includes the steps of mixing and stirring water and an emulsifier to obtain an emulsified solution by stirring for 10 to 20 minutes, further adding a plasticizer to the emulsified solution and continuing stirring and emulsification for 60 minutes ± 20 minutes, obtaining an emulsion and setting aside.
[0138] First, in the step of mixing and stirring the water and emulsifier, an emulsified solution is obtained by stirring for 10 to 20 minutes, and then a plasticizer is added to the emulsified solution and emulsified by stirring for 60 ± 20 minutes to obtain an emulsion, which is then kept as a reserve.
[0139] In some embodiments, the step of adding a prepolymer and an initiator to the emulsion, heating to react, and obtaining an adhesive includes the steps of adding the prepolymer and the initiator dropwise to the emulsion at a rate of 10 ml / min-500 ml / min, heating to react, and obtaining an adhesive after cooling.
[0140] In order to avoid introducing the prepolymer and the initiator into the emulsion together to cause explosive polymerization, the prepolymer and the initiator need to be slowly dripped into the emulsion, for example, the drip rate is 10 ml / min, 50 ml / min, 100 ml / min, 150 ml / min, 200 ml / min, 250 ml / min, 300 ml / min, 350 ml / min, 400 ml / min, 450 ml / min, 500 ml / min, etc., but is not specifically limited.
[0141] In some embodiments, the step of adding a prepolymer and an initiator to the emulsion and heating to react and obtain the adhesive includes the steps of adding a prepolymer and an initiator to the emulsion, heating to 90° C.±10° C., and stirring for 30 minutes±20 minutes to react and obtain the adhesive.
[0142] Since the initiator needs to start the monomer polymerization at a certain temperature, the prepolymer and initiator are added to the emulsion, heated to 90℃±10℃, and stirred for 30min±20min to react and obtain the adhesive.
[0143] In some embodiments, the prepolymer and initiator are added to an emulsion, heated to react, and the adhesive is obtained by the steps of adding a prepolymer and an initiator to an emulsion, heating to react, and adjusting the pH to 6-8 after cooling to obtain the adhesive.
[0144] The adhesive obtained by the production is prone to particle aggregation and deposition, which is disadvantageous for the use and storage of the adhesive. In order to avoid the aggregation and precipitation of the adhesive, a pH adjusting agent is added to the produced adhesive, so that the core-shell structured particles are uniformly dispersed and the system is stabilized. The pH range of the adhesive is pH 6-8, and may be, for example, pH 6, pH 7, pH 8, etc., and is not specifically limited. As can be understood, the present application does not limit the specific pH adjusting agent to be adopted, and the pH may be adjusted using, for example, ammonia water.
[0145] In some embodiments, in step 1, the mass of the emulsifier is 0.15% to 5% of the mass of the constituent monomers of the organic polymer, and in step 3, the mass of the initiator is 0.15% to 1% of the mass of the constituent monomers of the organic polymer.
[0146] The amount of emulsifier used must be moderate. The emulsifier is an important component of emulsion polymerization, and can convert mutually incompatible oil (monomer)-water into a fairly stable emulsion that is not prone to stratification. In emulsion polymerization systems, the emulsifier has three main functions: the first is to reduce surface tension and disperse the monomer as fine droplets; the second is to form a protective layer on the droplet or colloidal particle surface to prevent aggregation and keep the emulsion stable; and the third is to form micelles and solubilize the monomer. The size and number of micelles depend on the amount of emulsifier used, so the amount of emulsifier used directly affects the performance of the product. In step 1, the mass of the emulsifier is 0.15% to 5% of the mass of the constituent monomers of the organic polymer, and may be, for example, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 5%, etc., and is not specifically limited. The amount of initiator used has a large effect on the polymerization rate and the performance of the product. If the amount of initiator used is increased, the polymerization rate becomes faster, the polymerization reaction becomes unstable, the molecular weight and yield decrease, and the performance of the polymer also deteriorates. In addition, if the amount of initiator is insufficient, the polymerization reaction becomes difficult. Therefore, in step 3, the mass of the initiator is 0.15% to 1% of the mass of the constituent monomers of the organic polymer, and may be, for example, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1%, etc., and is not specifically limited.
[0147] In some embodiments, in steps 1 and 2, the emulsifier comprises an anionic emulsifier, and in step 3, the initiator comprises at least one of an azo initiator, an organic peroxide initiator, and an inorganic peroxide initiator.
[0148] Anionic emulsifiers are surface active materials whose active moieties tend to dissociate into negative ions when dissolved in water, and are characterized by having one large organic anion and being able to react with bases to form salts. Depending on the structure of the negative ion-carrying moiety, they are divided into three types: carboxylate, sulfonate, and sulfate.
[0149] Regarding the azo-based initiator, the azo-based initiator is a radical initiator whose molecular structure contains a nitrogen-nitrogen double bond.
[0150] Peroxide initiators are compounds that contain a peroxy group (-OO-), and when exposed to heat, the -OO- bond is broken and split into two corresponding radicals, thereby initiating monomer polymerization. They are called peroxide initiators. There are two types: inorganic peroxides and organic peroxides. Inorganic peroxide initiators include hydrogen peroxide, ammonium persulfate, or potassium persulfate, while organic peroxide initiators include benzoyl peroxide, benzoyl t-butyl peroxide, methyl ethyl ketone peroxide, etc.
[0151] The emulsifier is a material that can form water into an emulsion state, and the specific type and structure of the emulsifier are not limited in this application, and any material that can perform the above function and does not affect the reaction system can be applied to this application, for example, in steps 1 and 2, the emulsifier used includes an anionic emulsifier. The initiator is a material that can initiate the polymerization reaction of the monomer, and the specific type and structure of the initiator are not limited in this application, and any material that can perform the above function and does not affect the reaction system can be applied to this application, for example, in step 3, the initiator includes at least one of an azo initiator, an organic peroxide initiator, and an inorganic peroxide initiator.
[0152] In some embodiments, in steps 1 and 2, the emulsifier comprises at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, sodium styrene sulfonate, and sodium vinyl sulfonate, and in step 3, the initiator comprises at least one of azobisisobutyronitrile, azobisisoheptanonitrile, cumene hydroperoxide, tert-butyl hydroperoxide, benzoyl peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, and hydrogen peroxide.
[0153] The emulsifier is a substance capable of forming water into an emulsion state, and for example, the emulsifier used in steps 1 and 2 includes at least one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium dodecyl benzene sulfonate, sodium styrene sulfonate, and sodium vinyl sulfonate, i.e., the emulsifier used may be one of the above, and for example, preferably, the emulsifier is sodium dodecyl benzene sulfonate, and may be a mixture of two or more of the above. The initiator is a substance capable of initiating the polymerization reaction of a monomer, and for example, the initiator used in step 3 includes at least one of azobisisobutyronitrile, azobisisoheptanonitrile, cumene hydroperoxide, tert-butyl hydroperoxide, benzoyl peroxide, ammonium persulfate, potassium persulfate, sodium persulfate, and hydrogen peroxide, i.e., the initiator used may be one of the above, and for example, preferably, the initiator is potassium persulfate, and may be a mixture of two or more of the above.
[0154] In some embodiments, the combined mass of the water in step 1 and the water in step 2 comprises 30%-60% of the mass of all materials in steps 1, 2, and 3, and the water in steps 1 and 2 is deionized water.
[0155] Water has the functions of mass transfer and temperature control as a dispersion medium, and if the amount of water used is too little or too much, it is difficult to control the viscosity of the reaction system within a reasonable range, and the total mass of water in step 1, water in step 2 and water in step 3 accounts for 30%-60% of the mass of all materials in step 1, step 2 and step 3, for example, it can be 30%, 35%, 45%, 50%, 55%, 60%, etc., but is not specifically limited. At the same time, the water in step 1, step 2 and step 3 is deionized water, to avoid impurities in water affecting the polymerization reaction.
[0156] The embodiments of the present application further provide a separator, on which the above adhesive or the adhesive obtained by the above adhesive manufacturing method is provided. Since the adhesive adopts all the technical solutions of all the embodiments, it has at least all the beneficial effects of the technical solutions of the embodiments, and will not be further described here.
[0157] The separator is coated with the above adhesive, which can improve the adhesive performance between the electrode plate and the adhesive and improve the opening problem in the conventional battery core pre-cold pressing process.
[0158] The embodiments of the present application further provide an electrode assembly, which includes the above separator. The separator adopts all the technical solutions of all the above embodiments, and therefore has at least all the beneficial effects of the technical solutions of the above embodiments, and will not be further described here.
[0159] The electrode assembly includes a positive electrode plate, a negative electrode plate, and a separator, and the adhesive is coated on the separator, thereby bonding the electrode plate and the separator together and improving the problem of openings between the electrode plate and the separator.
[0160] The embodiments of the present application further provide a battery cell, the battery cell including the above-mentioned electrode assembly, since the electrode assembly adopts all the technical solutions of all the above-mentioned embodiments, it has at least all the beneficial effects of the technical solutions of the above-mentioned embodiments, and will not be further described here.
[0161] By applying the above electrode assembly to a battery cell, the cycle performance of the large jig of the battery cell can be improved.
[0162] The embodiments of the present application further provide a battery, which includes the above-mentioned battery cell. The battery cell adopts all the technical solutions of all the above-mentioned embodiments, and therefore has at least all the beneficial effects of the technical solutions of the above-mentioned embodiments, and will not be further described herein.
[0163] The battery includes a battery module and a battery pack.
[0164] The embodiments of the present application further provide a power consumption device, which includes the above battery cell or the above battery. The battery cell or the battery adopts all the technical solutions of all the above embodiments, and thus has at least all the beneficial effects of the technical solutions of the above embodiments, and will not be further described herein.
[0165] The electrode assembly, battery cell, battery and power consuming device of the present application will be described below with appropriate reference to the drawings.
[0166] In one embodiment of the present application, an electrode assembly is provided.
[0167] In general, the electrode assembly includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During charging and discharging of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to be absorbed and released. The electrolyte serves to conduct ions between the positive electrode plate and the negative electrode plate. The separator is disposed between the positive electrode plate and the negative electrode plate, and serves mainly to prevent short circuiting of the positive and negative electrodes, while allowing ions to pass through. The separator is the improved separator described above in this application.
[0168] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector.
[0169] For example, the positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and the positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.
[0170] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0171] In some embodiments, when the electrode assembly is a lithium ion battery, the positive electrode active material may adopt a positive electrode active material used in lithium ion batteries known in the art. For example, the positive electrode active material may include at least one material selected from the group consisting of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials in batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of the lithium transition metal oxide include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O2(NCM 333 (may be abbreviated as LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM 523 (may be abbreviated as LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (may be abbreviated as LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM 622 (may be abbreviated as LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05 Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.
[0172] In some embodiments, the positive electrode membrane layer further optionally includes an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0173] In some embodiments, the positive electrode membrane layer further optionally includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.
[0174] In some embodiments, the positive electrode plate can be manufactured in the following manner: The components for manufacturing the positive electrode plate, such as the positive electrode active material, conductive agent, adhesive and other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, which is then coated on a positive electrode current collector, and the positive electrode plate is obtained after processes such as drying and cold pressing.
[0175] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.
[0176] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.
[0177] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0178] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based materials, tin-based materials, and lithium titanate. The silicone-based material may be selected from at least one of silicon, silicone oxide, silicone carbon composite, silicone nitrogen composite, and silicone alloy. The tin-based material may be selected from at least one of tin, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.
[0179] In some embodiments, the negative electrode membrane layer further optionally comprises an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0180] In some embodiments, the negative electrode film layer further optionally comprises a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0181] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).
[0182] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.
[0183] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application does not specifically limit the type of electrolyte, which can be selected according to needs.
[0184] In some embodiments, the electrolyte is an electrolytic solution, which includes an electrolyte salt and a solvent.
[0185] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.
[0186] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.
[0187] In some embodiments, the electrolyte solution further optionally includes additives. For example, the additives may include an anode film-forming additive, a cathode film-forming additive, and may further include additives that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature or low temperature performance of the battery, etc.
[0188] In some embodiments, the electrode assembly further includes a separator. The present application is not particularly limited to the type of separator, and any known porous structure separator having good chemical and mechanical stability may be selected.
[0189] In some embodiments, the separator may be made of at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film, without any particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without any particular limitation.
[0190] In some embodiments, the positive and negative plates and the separator can be fabricated into an electrode assembly by a winding or lamination process.
[0191] In some embodiments, the electrode assembly may include an outer casing, which may be used to package the electrode assembly and electrolyte.
[0192] In some embodiments, the exterior of the electrode assembly may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the electrode assembly may be a pouch, such as a bag-like pouch. The pouch may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0193] The present application is not particularly limited to the shape of the electrode assembly, which may be cylindrical, rectangular, or any other shape. For example, FIG. 5 shows a battery cell 5 with a rectangular structure as an example.
[0194] In some embodiments, referring to FIG. 6, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is infiltrated into the electrode assembly 52. The number of electrode assemblies 52 included in the battery cell 5 may be one or more, and can be selected by those skilled in the art according to specific actual needs.
[0195] In some embodiments, the electrode assemblies may be assembled into a battery module, and the number of electrode assemblies included in the battery module may be one or more, and the specific number may be selected by one skilled in the art according to the application and capacity of the battery module.
[0196] Fig. 7 shows an example of a battery module 4. Referring to Fig. 7, in the battery module 4, the multiple battery cells 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, the multiple battery cells 5 may be arranged in any other manner. Furthermore, the multiple battery cells 5 may be fixed by fasteners.
[0197] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple battery cells 5 are accommodated in the accommodating space.
[0198] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number may be selected by one skilled in the art according to the application and capacity of the battery pack.
[0199] 8 and 9 show an example of a battery pack 1. Referring to Fig. 8 and Fig. 9, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0200] The present application further provides a power consuming device, which includes at least one of the electrode assembly, the battery module, or the battery pack according to the present application. The electrode assembly, the battery module, or the battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0201] As the power consuming device, an electrode assembly, a battery module or a battery pack can be selected according to the usage demand.
[0202] 10 is an example of a power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power and high energy density of the electrode assembly of the power consuming device.
[0203] Another example of the device may be a mobile phone, a tablet computer, a notebook computer, etc. This device is generally required to be thin, and employs an electrode assembly as a power source.
[0204] Working Example The following describes the examples of the present application. The examples in the following description are examples and are only used to interpret the present application, and should not be understood as limitations on the present application. If no specific techniques or conditions are specified in the examples, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. If no manufacturer is specified, the reagents or equipment used are all ordinary products available on the market.
[0205] Example 1 Adhesive manufacturing Step 1: Add 75.24g of methyl acrylate, 18.55g of acrylonitrile, and 6.21g of acrylamide into a 500mL three-neck flask, with the molar ratio of the three being 1:0.4:0.1; add 3.6g of sodium dodecylsulfonate and 150g of deionized water; stir thoroughly for 60 minutes to disperse and emulsify, and obtain the prepolymer of the encapsulant, which is then placed in a container for storage; Step 2: Add 100ml deionized water and 0.15g sodium dodecylbenzenesulfonate to a 500ml three-neck flask, emulsify for 10min at a rotation speed of 5000r / min after uniform stirring, then add 10g dibutyl phthalate and continue emulsifying for 60min to obtain a uniform and stable emulsion; Step 3: The encapsulant prepolymer prepared in step 1 and the initiator solution (0.2 g of the initiator potassium persulfate is dissolved in deionized water to form a solution) are slowly dripped in using a peristaltic pump. After dripping is complete, the temperature is raised to 90°C and the reaction is carried out by keeping the temperature for 0.5 hours. The mixture is then cooled to 40°C and the pH is adjusted to 7-8 with ammonia water, after which it is filtered and discharged.
[0206] Separator manufacturing A commercially available PP-PE copolymer microporous film (manufactured by Zhuo Gao Electronics Technology Co., Ltd., model number 20) with a thickness of 20 μm and an average pore diameter of 80 nm was used as the substrate. The adhesive prepared as above was uniformly stirred and mixed in deionized water to obtain a slurry (solid content 20%). The slurry was uniformly applied to two surfaces of the substrate, dried to remove the solvent, and the composition was coated on the substrate at a coating density of 1.0 g / m. 2 Thus, a separator was obtained.
[0207] Positive electrode plate manufacturing Polyvinylidene fluoride (PVDF), lithium iron phosphate (LFP), carbon black as a conductive agent, and N-methylpyrrolidone (NMP) were mixed homogeneously in a mass ratio of 1.2:58.38:0.42:40, and then prepared as a positive electrode slurry. This positive electrode slurry was mixed at 200 g / m 2 The positive electrode current collector aluminum foil was uniformly coated with the coating solution at a loading amount of 1000g, and then dried, cold pressed, and cut to obtain a positive electrode plate.
[0208] Negative electrode plate manufacturing Artificial graphite, acetylene black as a conductive agent, styrene butadiene rubber (SBR) as an adhesive, and sodium carboxymethylcellulose (CMC-Na) as a thickener were added to deionized water in a mass ratio of 96.2:1.0:1.6:1.2, thoroughly stirred to mix uniformly, and then anode slurry (solid content 63%) was produced. This anode slurry was 98 g / m 2 The negative electrode current collector copper foil was coated with the coating solution at a loading amount of 1000g, and then dried, cold pressed, and cut to obtain a negative electrode plate.
[0209] Electrolyte production At 25°C, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed solvent, and LiPF6 is dissolved in the mixed solvent to obtain an electrolyte solution, in which the concentration of LiPF6 is 1 mol / L.
[0210] Electrode assembly fabrication The positive electrode plate, separator, and negative electrode plate were stacked in this order, wound, and pre-press molded (the separator and the electrode plate were bonded during this period) to obtain an electrode assembly. The electrode assembly was then placed in an outer casing, the above-prepared electrolyte solution was added, and the electrode assembly was obtained after going through processes such as packaging, standing, chemical conversion, and aging.
[0211] The parameters (eg, as shown in Tables 1 and 2) of Example 1 were changed to obtain the experimental data of Examples 2 to 18.
[0212] Example 12 15g of urea, 38.01g of formaldehyde solution, 1.5g of ammonium chloride, 1.5g of resorcinol, 1.5g of sodium dodecylbenzenesulfonate and 100g of deionized water were added to a 250ml four-neck flask as the continuous phase of the reaction. Stirring was started, and after stirring and dissolving, the pH value was adjusted to 4 with HCl solution, and 5g of dibutyl phthalate was added and emulsified at a stirring speed of 30min. After the solution temperature was raised to 60℃, the reaction continued for 4h and the reaction was completed. After cooling, the microcapsule aqueous solution was suction filtered, washed with a large amount of deionized water, filtered and dried.
[0213] Comparative Example 1: Preparation of polyacrylate-based polymer At room temperature, 60.92g of methyl acrylate, 33.04g of acrylonitrile and 6.04g of acrylamide were weighed and added into a 500mL four-neck flask equipped with a mechanical stirrer, a thermometer and a condenser. 3g of sodium dodecyl sulfate emulsifier, 1g of ammonium persulfate initiator and 120g of deionized water were added, and the mixture was emulsified by stirring at a rotation speed of 1600 rpm for 30 minutes. The mixture was then heated to 75℃ and reacted for 4 hours. The pH value was adjusted to 6-8, and the mixture was cooled to below 40℃ to stop the reaction, filtered and discharged.
[0214] Comparative Example 2: Steps for preparing a polymer obtained by polymerizing a first flexible monomer In a three-neck flask, 752.4 g of methyl acrylate, 36 g of sodium dodecylsulfonate, and 1.2 kg of deionized water were added, and the mixture was thoroughly stirred to disperse and emulsify. The temperature was raised to 70°C, and an initiator solution (a solution formed by dissolving 0.6 g of potassium persulfate in deionized water) was added, and the mixture was reacted with stirring for 30 minutes. The temperature was continued to be raised to 80°C, and an initiator solution (a solution formed by dissolving 1.2 g of potassium persulfate in 100 g of deionized water) was slowly dripped using a peristaltic pump. After the dripping was completed, the temperature was raised to 90°C and the mixture was reacted while keeping the temperature constant for 0.5 hours. The mixture was then cooled to 40°C, and the pH was adjusted to 7 with ammonia water, the reaction was stopped, and the mixture was filtered and discharged.
[0215] Comparative Example 3: Steps for preparing a polymer obtained by polymerizing a second polymerizable polar monomer Deionized water and a certain percentage of initiator were added to a three-neck flask containing a reflux condenser, a thermometer, and a stirring magnetron. After stirring uniformly at room temperature, the mixture was heated to the set temperature to promote the decomposition of the initiator. About half an hour after the temperature became constant, a peristaltic pump was used to control the concentration of acrylonitrile in the polymerization system, and the monomer was dripped into the water in a small droplet method to achieve the polymerization reaction. After the monomer dripping was completed, the reaction was continued at a constant temperature for a certain period of time while stirring. After the reaction was completed, the three-neck flask was transferred to the air and cooled to room temperature to stop the reaction, filtered, and discharged.
[0216] Comparative Example 4: Steps for Producing a Polymer Obtained by Polymerizing a Third Polymerization Molecular Weight Control Monomer First, 120g of water was added to 30g-90g of acrylamide monomer to prepare an acrylamide solution, and 0.02g-1g of persulfate was dissolved in 30g of water to obtain an initiator solution. 37.5g of isopropyl alcohol solvent was added to a 250mL four-neck reaction flask, opened and stirred, the stirring speed was set to 200r / min, the temperature was raised to reflux, and the monomer solution and the initiator solution were continuously dripped, the dripping speed was controlled, and the dripping time was set to 120min. The reflux reaction was maintained for 2h, the isopropyl alcohol was distilled, and a polyacrylamide solution was obtained, filtered, and discharged.
[0217] Comparative Example 5: Preparation of a polymer obtained by mixing a plasticizer and a polyacrylate and polymerizing the mixture The polyacrylate solution produced in Comparative Example 1 and dibutyl phthalate as a plasticizer were mixed in a mass ratio of 100:5 and stirred uniformly to obtain a mixed solution of polyacrylate and plasticizer.
[0218] Comparative Example 6: Preparation steps of polymer obtained with melamine resin encapsulant component Preparation of wall material melamine resin: wall material was prepared with melamine:formaldehyde:water in a mass ratio of 1:2:5. First, 45.0g of deionized water was added to 15.0g of melamine and 30.0g of formaldehyde solution, and triethanolamine was added dropwise to adjust the pH to 8-9. The mixture was stirred in a 70℃ water bath and heated until the wall material became transparent, after which 30.0g of deionized water was added and the mixture was stirred for 30 minutes to obtain the wall material.
[0219] Capsule preparation: 71.91g of distilled water and 0.09g of sodium dodecylbenzenesulfonate were mixed and stirred for 10min, and then 9g of dibutyl phthalate was added. Stirred in a 70℃ water bath for 60min, thereby obtaining a core emulsion, and the cooled wall material melamine resin was slowly added to the core emulsion, and citric acid was added to the mixed solution to adjust the pH value to 2.5-3.0. The mixture was slowly heated to 70℃ and stirred for 3h to stop the reaction. After standing at room temperature, the obtained product was washed with deionized water and absolute ethanol and filtered multiple times. Finally, the obtained product was placed in a 40℃ oven to heat and dry for 48h, and the obtained powder is a microcapsule coated with melamine resin.
[0220] As shown in Tables 1 and 2, in Examples 1 to 4, 17 and 18, the ratio of the three types of polymers in the capsule shell was changed while keeping other conditions unchanged; in Examples 5 to 8, 13 to 16, the masses of the core material and capsule shell were changed while keeping other conditions unchanged; and in Examples 9 to 11, the volume average particle size Dv50 of the adhesive was changed while keeping other conditions unchanged.
[0221] As shown in Table 3, Comparative Example 1 is an adhesive made of an acrylate copolymer obtained by copolymerizing methyl acrylate, acrylonitrile, and acrylamide, Comparative Example 2 is an adhesive made of a polymer obtained by polymerizing acrylonitrile, Comparative Example 3 is an adhesive made of a polymer obtained by polymerizing acrylamide, Comparative Example 4 is an adhesive made of a polymer obtained by polymerizing acrylamide, Comparative Example 5 is an adhesive made of a polymer obtained by mixing and polymerizing a plasticizer and a polyacrylate copolymer, and Comparative Example 6 is an adhesive obtained by manufacturing using melamine resin as the capsule shell and a plasticizer as the core material.
[0222] [Table 1]
[0223] [Table 2]
[0224] [Table 3]
[0225] Performance Test: 1. Separator and electrode plate adhesion test step The battery plate and separator were stacked and placed in a heat press, and the heat press parameters were set to 25°C, 10t, and 30s, and pressure was applied to produce a bonded separator / positive plate sample, which was then cut into a 150 x 20mm rectangular spline. One side of the rectangular spline plate was attached to a steel plate with double-sided adhesive, and the separator and plate were separated by a length of 2cm along the length at one end of the rectangular spline to produce a test sample.
[0226] The steel plate was held horizontally and fixed to the lower fixture of a universal testing machine (Xieqiang Machinery Manufacturing (Shanghai) Co., Ltd., model number CTM2100), and the peeled end of the separator was fixed to the upper fixture of the universal testing machine and a tensile machine was connected. The test conditions were set to a tensile rate of 20 mm / min and a horizontal tensile of 10 cm. Once the tensile force was stable, the tensile force value was recorded, and the adhesive strength between the separator and the electrode plate was obtained by the ratio of the tensile force value to the sample width. At the same time, the adhesive strength data between the separator and the electrode plate can indirectly explain the adhesive performance of the adhesive, and the better the adhesive performance, the greater the adhesive strength data between the separator and the electrode plate.
[0227] 2. Battery core hardness test steps The battery core was placed on horizontal tables at both ends, the width of the central openwork part was fixed at 12 cm, the battery core was laid naturally flat, and the deviation of the center of the battery core from the horizontal reference line was measured, and the hardness of the battery core was evaluated based on this. It was explained that the greater the deviation of the center of the battery core from the horizontal reference line, the worse the hardness of the battery core.
[0228] 3. Cycle performance test step At 25°C, the battery produced in Example 1 is charged at a constant current of 1 / 3C to 3.8V, then charged at a constant voltage of 3.8V until the current becomes 0.05C, left for 5 minutes, and discharged at 1 / 3C to 2.0V, the resulting discharge capacity is the initial capacity C0, and the above steps are repeated for the same battery, and the discharge capacity Cn of the battery after the nth cycle is recorded at the same time. The battery capacity retention rate after each cycle is Pn = (Cn / C0) x 100%. That is, the difference in cycle performance can be embodied in the battery capacity retention rate after 500 cycles.
[0229] [Table 4]
[0230] As shown in Table 4, the battery cores obtained using the adhesives in Examples 1 to 18 have good adhesive strength between the separator and the electrode plate, but the battery cores obtained using the adhesives in Comparative Examples 1 to 6 have adhesive strength between the separator and the electrode plate that is not as good as that in Examples 1 to 18. It has been explained that the adhesive performance of the adhesives in Examples 1 to 18 is superior to that of the adhesives in Comparative Examples 1 to 6. And, the battery cycle performance in Examples 1 to 18 is superior to that of Comparative Examples 1 to 6. It has been explained that when the adhesive performance of the adhesive is improved, the cycle performance of the battery can be effectively improved by using this adhesive for the battery separator.
[0231] The above is merely a preferred embodiment of the present application, and does not limit the patent scope of the present application. Any equivalent structural transformation made using the contents of the specification and drawings of the present application in accordance with the application concept of the present application, or any direct or indirect operation in other related technical fields, is within the patent protection scope of the present application. [Explanation of symbols]
[0232] 1. Battery pack 2. Upper case 3. Lower case 4. Battery module 5. Battery cell 51…Case 52...Electrode assembly 53…Cover plate 6...Capsule shell structure 7...Core material
Claims
1. 1. An adhesive comprising: a capsule shell and a core material disposed within the capsule shell, the capsule shell comprising an organic polymer, and the core material comprising a plasticizer.
2. The adhesive of claim 1, wherein the weight ratio of said organic polymer to said plasticizer is 1:(10-100), optionally 1:(20-90).
3. The adhesive of claim 1 or 2, wherein the adhesive has a volume average particle size Dv50 of 0.5 μm-100 μm, optionally 7 μm-8 μm.
4. The adhesive according to claim 1 , wherein the organic polymer comprises at least one of a polyacrylate-based polymer and a urea-formaldehyde resin.
5. The adhesive according to claim 4 , wherein constituent monomers of the polyacrylate polymer include a first polymerizable flexible monomer, a second polymerizable polar monomer, and a third polymerizable molecular weight adjusting monomer.
6. 6. The adhesive of claim 5, wherein the molar ratio of the first polymerizable flexible monomer to the second polymerizable polar monomer to the third polymerizable molecular weight adjusting monomer is 1:(0.01-0.8):(0.01-0.15), optionally 1:(0.05-0.7):(0.05-0.12).
7. 7. The adhesive according to claim 5 or 6, wherein the structure of the first polymerizable flexible monomer contains an ester bond, the structure of the second polymerizable polar monomer contains a cyano group, and the structure of the third polymerizable molecular weight adjusting monomer contains an amide bond.
8. 8. The adhesive of claim 5, wherein the first polymerizable flexible monomer is an acrylate-based monomer, the second polymerizable polar monomer is an acrylonitrile-based monomer, and the third polymerizable molecular weight adjusting monomer is an acrylamide-based monomer.
9. The acrylate monomer includes at least one of methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, n-propyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate; And / or, the acrylonitrile-based monomer includes at least one of acrylonitrile and methacrylonitrile, And / or the acrylamide monomer includes at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide.
10. The adhesive of any one of claims 1 to 9, wherein the plasticizer comprises at least one of dibutyl phthalate, dioctyl adipate, dibutyl sebacate, dioctyl sebacate, and di-n-butyl adipate.
11. A method for producing an adhesive, comprising the steps of: mixing and stirring water, an emulsifier and constituent monomers of an organic polymer to obtain a prepolymer, which is kept as a reserve; Mixing and stirring water, an emulsifier, and a plasticizer to obtain an emulsion, which is then reserved; A method for producing an adhesive, comprising: adding the prepolymer and an initiator to the emulsion and heating to react them to obtain an adhesive, the adhesive comprising a capsule shell and a core material disposed within the capsule shell, the capsule shell comprising an organic polymer, and the core material comprising a plasticizer.
12. The method of claim 11 , wherein the organic polymer comprises at least one of a polyacrylate-based polymer and a urea-formaldehyde resin.
13. The method for producing an adhesive according to claim 11 or 12, wherein the ratio of the mass of the plasticizer to the mass of the constituent monomers of the organic polymer is 1:(10 to 100), and optionally 1:(20 to 90).
14. A separator, comprising an adhesive provided on the separator, the adhesive being manufactured by the adhesive manufacturing method according to any one of claims 1 to 10 or claims 11 to 13.
15. An electrode assembly comprising the separator of claim 14.
16. A battery cell comprising the electrode assembly of claim 15.
17. A battery comprising the battery cell of claim 16.
18. 18. A power consuming device comprising a battery cell according to claim 16 or a battery according to claim 17.
Citation Information
Patent Citations
Heat-sensitive pressure-sensitive adhesive material
JP2002121533A
Microcapsule and its manufacturing method
JP2009509750A
Article containing on-demand adhesive microcapsules and method for producing same
JP2017502177A
Binders and associated separators, plates, batteries, battery modules, battery packs and power consuming devices
JP2024519417A
Method for producing solid particles using microchannel structure
JP4385886B2